2012
DOI: 10.1029/2012gc004384
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy, magnetostatic interactions and identification of magnetofossils

Abstract: [1] Single-domain magnetite particles produced by magnetotactic bacteria (MTB) and aligned in chains, called magnetosomes, are potentially important recorders of paleomagnetic, paleoenvironmental and paleolife signals. Rock magnetic properties related to the anisotropy of magnetosome chains have been widely used to identify fossilized magnetosomes (magnetofossils) preserved in geological materials. However, ambiguities exist when linking magnetic properties to the chain structure because of the complexity of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
150
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(164 citation statements)
references
References 98 publications
14
150
0
Order By: Relevance
“…As shown in figure 2b, the abrupt decrease in remanence around 100-110 K on the thermal decays of saturation remanence magnetization acquired at 2.5 T field at 10 K (SIRM 2.5T_10K ) after cooling in a field of 2.5 T (FC) or zero (ZFC) indicates the Verwey transition of magnetosome magnetite, as observed in previous studies [41]. The difference between the remanence losses of FC (d FC ) and ZFC (d ZFC ) curves upon warming across the Verwey transition, quantitatively described as d FC /d ZFC , is related to the chain configuration of magnetosomes [31,35,41]. As expected, the Verwey transition behaviours of the magnetosomes are distinctly different among the three cultures ( figure 2b,e,h).…”
Section: Magnetic Propertiesmentioning
confidence: 74%
“…As shown in figure 2b, the abrupt decrease in remanence around 100-110 K on the thermal decays of saturation remanence magnetization acquired at 2.5 T field at 10 K (SIRM 2.5T_10K ) after cooling in a field of 2.5 T (FC) or zero (ZFC) indicates the Verwey transition of magnetosome magnetite, as observed in previous studies [41]. The difference between the remanence losses of FC (d FC ) and ZFC (d ZFC ) curves upon warming across the Verwey transition, quantitatively described as d FC /d ZFC , is related to the chain configuration of magnetosomes [31,35,41]. As expected, the Verwey transition behaviours of the magnetosomes are distinctly different among the three cultures ( figure 2b,e,h).…”
Section: Magnetic Propertiesmentioning
confidence: 74%
“…It displays narrow size distributions and is in the magnetic stable single-domain range. Magnetosome chains have remarkable magnetic properties (5,6,9), which have been used to identify bacterial magnetofossils in sediments. Although previous studies demonstrated that observations by electron microscopy and/or magnetic measurements could detect bacterial magnetofossils in natural samples (9)(10)(11)(12)(13), the chain structure is generally lost during sediment aging owing to degradation of organic matter assembling magnetosomes (9,14).…”
mentioning
confidence: 99%
“…Derived magnetic susceptibility is generally x ¼ k 3 /(BcVT) and equals (2.5 + 0. The superparamagnetic magnetite exhibits a relatively strong magnetic moment, so we derived its low-field susceptibility from magnetization of dry magnetite sample at five temperature points (figure 4) above the Verwey transition, which is typically less than 123 K [31,32]. The low-field susceptibility is x ¼ q 4 /(m 1 T ) and equals (3 [33] and their packing in corpuscles characterized by factor P ¼ 0.7.…”
mentioning
confidence: 99%